Successful Therapeutic Management of Cystoisospora Infection in Dog - KR. Baghel; I. L. Raj; S. Bisen; H. K. Ratre (The Indian Veterinary Journal, 2024)
Three young male dogs (two Labrador and one German shepherd) were presented with the complaint of weakness; fever, weight loss, dyspnoea and diarrhea. The coccidian oocysts were observed by examine faeces using direct smear method and floatation techniques. The oocysts were identified as Cystoisospora coccidia on sporulation. The oocysts were measured 18 – 21 µm x 19 – 23µm using micrometry and confirmed as C. ohioensis complex. The dogs were cured using sulphamethoxazole + trimethoprime (tab septran) and fluid therapy with dextrose normal saline, ringers lactate, parentral multivitamins. Meloxicam and paracetamol (melonex plus) administered only in febrile condition. Significant improvement on health was noticed 10 days post treatment.